Analysis of the effect of temperature on protein abundance in Demodex-associated Bacillus oleronius. Issue 4 (10th April 2018) - Maher, Amie; Staunton, Kara; Kavanagh, Kevin
Abstract: A potential role for bacteria in the induction of rosacea has been suggested. The aim of this work was to characterise the effect of temperature on the production of immunostimulatory proteins by Bacillus oleronius —a bacterium to which rosacea patients show sera reactivity and which was originally isolated from a Demodex mite from a rosacea patient. The affected skin of rosacea patients is at a higher temperature than unaffected skin, and it was postulated that this might alter the protein expression pattern of B. oleronius . B. oleronius growth was reduced at 37°C compared to 30°C but resulted in increased expression of the immune-reactive 62kDa protein (1.65 fold [ P < 0.05]). Proteomic analysis revealed increased abundance of a wide range of proteins involved in the stress response (e.g. stress proteins [21.7-fold increase], phosphocarrier protein HPr [438.5-fold increase], 60 kDa chaperonin [12.6-fold increase]). Proteins decreased in abundance after growth at 37°C included ferredoxin (325-fold decrease) and peptidase (244-fold decrease). This work indicates that the increased skin temperature of rosacea patients may alter the growth and protein production pattern of B. oleronius and lead to the greater production of immuo-stimulatory proteins. Abstract : The elevated temperature of rosacea skin may alter protein production by a bacterium implicated in its induction.